2016
DOI: 10.1200/jco.2015.65.3642
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Multicenter, Randomized, Double-Blind Controlled Study of Efficacy and Safety of Umbilical Cord–Derived Mesenchymal Stromal Cells in the Prophylaxis of Chronic Graft-Versus-Host Disease After HLA-Haploidentical Stem-Cell Transplantation

Abstract: Our findings suggest that the repeated infusion of MSCs might inhibit cGVHD symptoms in patients after HLA-haplo HSCT, accompanied by changes in the numbers and subtypes of T, B, and NK cells, leading to the acquisition of immune tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 54 publications
2
129
0
2
Order By: Relevance
“…In our previous clinical practice, MMF and tacrolimus were used from day −7 to prevent GVHD. [19][20][21] In this study, the use of MMF and tacrolimus, which can kill the T cells and thus might be harmful to CAR-T cells, was changed from day −7 to day 1 after the third day of the last infusion of CAR-T cells. This approach was adopted to avoid or alleviate the killing and the inhibition of the proliferation of the CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous clinical practice, MMF and tacrolimus were used from day −7 to prevent GVHD. [19][20][21] In this study, the use of MMF and tacrolimus, which can kill the T cells and thus might be harmful to CAR-T cells, was changed from day −7 to day 1 after the third day of the last infusion of CAR-T cells. This approach was adopted to avoid or alleviate the killing and the inhibition of the proliferation of the CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided encouraging results regarding the utility of UC-MSCs in several disease models, such as rescuing visual functions in a rodent model of retinal disease14, alleviating neuropathic pain15, protect against experimental colitis16 and treating rat liver fibrosis1718. The use of UC-MSCs as a cellular therapy is currently being explored in clinical trials, including for the treatment of GvHD1920.…”
mentioning
confidence: 99%
“…Although several studies using a mouse bone marrow transplant (BMT) model 9 have identified Tregs, myeloid-derived suppressor cells, and MSCs as available strategies for GVHD alleviation, none of them can be routinely applied in clinic. 10,11 Regulatory B cells (Bregs) are a newly described subset of B cells that appears to play important roles in autoimmunity. [12][13][14][15][16][17] Human Bregs were enriched in both transitional (CD24 …”
Section: Cd25mentioning
confidence: 99%